What pathological embodiment/disembodiment tell us about body representations. (December 2020) - Garbarini, F.; Fossataro, C.; Pia, L.; Berti, A.
Abstract: In the last decade, a considerable amount of studies investigated different neuropsychological syndromes related to the disorder of body awareness. In this paper, we shall review neuropsychological evidence of pathological embodiment/disembodiment conditions with the aim of describing the major common features, and the complementary characteristics, that may suggest the structure and function of a shared body representation. In particular, we shall first discuss experimental studies conducted on a bizarre disorder of body ownership we recently described [i.e., brain-damaged patients claiming that another person's hand belongs to them (Pathological Embodiment, PE)]. Then complementary syndromes, with an apparent opposite attitude with respect to the PE (i.e., somatoparaphrenia and xenomelia, which is part of the Body Integrity Identity Disorders) will be also considered. We shall discuss the behavioural similarities/differences between these complementary disturbances also referring to already existing conceptual knowledge and proposals about body representation. Highlights: Pathological embodiment/disembodiment conditions are reviewed. Behavioral/physiological characteristic of this pathologies are described. Similarities/differences between complementary disturbances are discussed. Explanations of the observed symptoms are proposed.